2015
DOI: 10.7326/m14-1551
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Type 2 Diabetes Mellitus: Relationship of Body Mass Index to Prognosis

Abstract: National Institute for Health Research and University of Hull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
159
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(177 citation statements)
references
References 46 publications
18
159
0
Order By: Relevance
“…In summary, the U-shaped relationship was reported in eleven studies (6)(7)(8)10,16,19,(21)(22)(23)(24)26). The lowest risk of mortality was found in patients with overweight in eight out of eleven studies (6)(7)(8)16,21,22,24,26), and in those with obesity in other three studies (10,19,23). In contrast, three studies found that an inverse rather than a U-shaped relationship between BMI and all-cause mortality (17,18,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the U-shaped relationship was reported in eleven studies (6)(7)(8)10,16,19,(21)(22)(23)(24)26). The lowest risk of mortality was found in patients with overweight in eight out of eleven studies (6)(7)(8)16,21,22,24,26), and in those with obesity in other three studies (10,19,23). In contrast, three studies found that an inverse rather than a U-shaped relationship between BMI and all-cause mortality (17,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow-up period was from 2.7 years (23) to 16 years (22). In all studies, the HRs were obtained by the adjustments for traditional vascular risk factors, and in some studies, the HRs were additionally controlled for other confounding factors, such as duration of diabetes (6,16,17,21,22,24,25), diabetic complications (9,21), menopause status (7,18), comorbid condition (16,18), and glomerular filtration rate (10).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study investigating the relationship between BMI and mortality in 10,568 people with type 2 diabetes found a lower mortality risk in overweight (BMI ≥25 kg/m 2 ), higher mortality risk in underweight (≤18.5 kg/m 2 ), and a similar mortality risk in obese (BMI ≥30 kg/m 2 ) people compared with those with normal weight, indicating a nonlinear association between BMI and all-cause mortality [12]. A recent systematic review including nine studies reported a reduced risk of all-cause mortality in overweight and obese people with type 2 diabetes when compared with normal or non-overweight people and a 5% progressive decrease in mortality for every 5 kg/m 2 increase in BMI [13].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity contributes to the etiologies of various comorbid conditions, such as cardiovascular disease, hypertension and type 2 diabetes (Wendel et al, 2008;Costanzo et al, 2015). In addition to storing lipid for energy, adipose secretes a variety of adipokines, many of which affect metabolism and inflammation in adipose and non-adipose tissues.…”
Section: Introductionmentioning
confidence: 99%